Mapping Student Scholarship Recipients With QGIS Cloud di Kabupaten Probolinggo - Moh Jasri; Ranu Setyobudi; Sulis tiyanto (Universitas Islam Lamongan, 2018)
This research was carried out to overcome one of the main problems faced in the lack of information about the scholarship recipient students (scholarship) in Probolinggo district as well as reporting in the form of a map of the location of the student's domicile. GIS Cloud can display the distribution of scholarship recipients in the area of Probolinggo Regency so that it can be enjoyed by the wider community. The system development methodology used in this research is the Waterfall method. The results of this study are maps of online distribution of students receiving scholarships that display information on student data, with a background map of the sub-district boundaries of Probolinggo Regency.